Activation of NLRP3 Inflammasome and Onset of Alzheimer’s Disease - Bai, Hua; Zhang, Qifang (Frontiers in Immunology, 2021)
The nucleotide-binding domain leucine-rich repeat and pyrin domain containing receptor protein 3 (NLRP3) is an important pattern recognition receptor in human innate immunity. Activation of the NLRP3 inflammasome play a key role in the pathogenesis of Alzheimer's disease (AD). Theories explaining activation of the NLRP3 inflammasome include the reactive oxygen species theory, the lysosomal damage theory and the mitochondrial DNA theory. The NLRP3 activation promotes occurrence of AD by producing IL-1β, IL-18 and other cytokines, and then by affecting the deposition of Aβ and tau proteins. Over-activated NLRP3 inflammasome often impair cell function and induces immune-related diseases. Some mechanisms have been found to negatively regulate activation of the NLRP3 inflammasome, which may be through receptor binding blocking mechanism, autophagy related mechanism, abnormal cytokine secretion mechanism, or interference related gene expression regulation mechanism. In this review, we summarize the possible mechanisms by which the activation of NLRP3 inflammasomes affects the pathogenesis of AD, and the recent advances in the prevention and treatment of AD by controlling the activation of NLRP3 inflammasomes. By researching the activation or inactivation of NLRP3 inflammasome, it is possible to reveal the pathogenesis of AD from a new perspective and provide a new idea for the prevention and treatment of AD.